The benchmarking sourcebook how to find the right benchmarking partners - Cross, Michael (B.T. Batsford, 1998)
A guide for companies seeking compatible partners when engaged in benchmarking studies. It lists details of a wide range of companies to enable those involved to find another company of comparable size and make-up with whom to benchmark. Business students may also find this a useful reference.